Paving the way towards effective entrepreneurship education in private higher educational institutions in emerging economy: An analysis of barriers and strategies - Mahi Uddin; Harun Bal; Nazamul Hoque (Sustainable Futures, 2025)
This study aims to investigate the barriers to and strategies for entrepreneurship education (EE) in higher education institutions (HEIs) in Bangladesh. We employed a qualitative approach, conducting 22 semi-structured interviews with current students, alumni, teachers, and employers. Drawing on institutional theory and the theory of planned behavior (TPB), the findings revealed numerous barriers to EE, including issues related to collaboration, economic constraints, regulatory hurdles, socio-cultural factors, lack of access to platforms, insufficient support, ICT-related challenges, gaps in skills and knowledge, curriculum design, assessment practices, shortcomings in the education system, lack of aspiration, and financial and attitudinal obstacles. The study also identified several strategies for HEIs to adopt to enhance the effectiveness of EE. These include fostering and supporting the development of a dynamic entrepreneurial ecosystem, promoting instrumental collaboration, embracing innovation and technology, implementing entrepreneurship-centric curricula, increasing the number of entrepreneurial educators, establishing incubator classrooms, encouraging social entrepreneurship, and providing governmental and societal support. We argue that this is one of the early studies to integrate TPB and institutional theory to examine the barriers and strategies for effective EE, offering novel insights into the EE landscape within the private HEI sector of a developing country. The findings can inform academics, researchers, regulators, alumni, entrepreneurs, and policymakers, helping them promote and better understand EE as a viable pathway to address educated youth unemployment and contribute to building a sustainable Bangladesh.